Significance between Organizational Culture and Lecturer Performance of Private Universities in Medan - Aisyah, Nur; Ambarita, Biner; Sibuea, Abdul Muin (Budapest International Research and Critics University, 2019)
This study discusses about how significance between organizational culture and lecturer perfomance. This research is a study that uses numerical numbers and changes feed approach to quantitative methods, with descriptive research that processes data with SPSS from the results of questionnaires on population samples. The research is done in private universities, college, academies and polytechnics in Medan. The result shows that organizational culture tends to be